Fast-Expanding Hi Shells Associated with Supernova Remnants in the I-GALFA Survey. Issue Volume 9:Issue S296(2013) (29th January 2014) - Park, Geumsook; Koo, Bon-Chul; Gibson, Steven J.; Kang, Ji-hyun
Abstract: We examine excess emission at high positive and negative velocities toward known Galactic supernova remnants (SNRs) in the "Inner-Galaxy Arecibo L-band Feed Array (I-GALFA)" Hi 21-cm survey data. The I-GALFA survey covers ℓ = 32° to 77°, and has a velocity range of ±700 km s −1 with high angular and velocity resolutions (4′ and 0.18 km s −1, respectively) and good sensitivity (0.2 K). The excess emission which is thought to be part of a fast-expanding Hi shell of a SNR is detected from four among 39 SNRs in the I-GALFA area: W44, G54.4–0.3, W51C, and CTB 80. Although the Hi shells of the four SNRs were already reported in low-resolution studies, the first detection of both sides of an expanding Hi shell associated with W44 is very inspiring. We discuss physical properties of these four SNRs and their statistical nature.